Two Novel Intronic Mutations in the CSF1R Gene in Two Families With CSF1R-Microglial Encephalopathy - Jiang, Jiwei; Li, Wenyi; Wang, Xiaohong; Du, Zhongli; Chen, Jinlong; Liu, Yaou; Li, Wei; Lu, Zhonghua; Wang, Yanli; Xu, Jun (Frontiers in Cell and Developmental Biology, 2022)
Objective: To describe two novel heterozygous splicing variants of the CSF1R gene responsible for CSF1R-microglial encephalopathy in two unrelated Han Chinese families and further explore the relationship between the pathological and neuroimaging findings in this disease. Methods: The demographic data, detailed medical history, and clinical manifestations of two unrelated Han families with CSF1R-microglial encephalopathy were recorded. Some family members also underwent detailed neuropsychological evaluation, neuroimaging, and genetic testing. The probands underwent whole-exome sequencing (WES) or next-generation sequencing (NGS) to confirm the diagnosis. The findings were substantiated using Sanger sequencing, segregation analysis, and phenotypic reevaluation. Results: Both families presented with a dominant hereditary pattern. Five of 27 individuals (four generations) from the first family, including the proband and his sister, father, uncle, and grandmother, presented with cognitive impairments clinically during their respective lifetimes. Brain magnetic resonance imaging (MRI) depicted symmetric, confluent, and diffuse deep white matter changes, atrophy of the frontoparietal lobes, and thinning of the corpus callosum. The proband’s brother remained asymptomatic; brain MRI revealed minimal white matter changes, but pseudo-continuous arterial spin labeling (pCASL) demonstrated a marked reduction in the cerebral blood flow (CBF) in the bilateral deep white matter and corpus callosum. Seven family members underwent WES, which identified a novel splice-site heterozygous mutation (c.2319+1C>A) in intron 20 of the CSF1R gene in four members. The proband from the second family presented with significant cognitive impairment and indifference; brain MRI depicted symmetric diffuse deep white matter changes and thinning of the corpus callosum. The proband’s mother reported herself to be asymptomatic, while neuropsychological evaluation suggested mild cognitive impairment, and brain MRI demonstrated abnormal signals in the bilateral deep white matter and corpus callosum. NGS of 55 genes related to hereditary leukodystrophy was performed for three members, which confirmed a novel splice-site heterozygous mutation (c.1858+5G>A) in intron 13 of the CSF1R gene in two members. Conclusions: Our study identified two novel splicing mutation sites in the CSF1R gene within two independent Chinese families with CSF1R-microglial encephalopathy, broadening the genetic spectrum of CSF1R-microglial encephalopathy and emphasizing the value of pCASL for early detection of this disease.